The Urgency of the Halal Slaughterhouse Concept with a Green Economy Approach - Hasanah, Hikmatul; Suharto, Babun; Rifa’i, Khamdan (LPPM, Universitas Islam Syarifuddin Lumajang, 2024)
The reality in the field is that the implementation of halal in slaughterhouses has not yet fulfilled its tayyib, this is because Sharia rules have not yet been entrenched and community traditions are still attached. This research aims to put forward the idea of ​​a halal slaughterhouse concept with a green economy approach which is expected to be applied to slaughterhouses in all regions, using qualitative research methods and library research. So this article puts forward the concept of halal abattoirs with a green economy approach because halal abattoirs alone do not guarantee their tayyib, so support is needed that can be accepted by abattoir managers. Green economy is important to include in the concept of halal slaughterhouses because green economy is not a commitment to religious teachings, but a global agreement that allows it to be accepted by society in general with different religious backgrounds. The research results show that the green economy supports sustainable development without causing environmental damage and does not conflict with Islamic concepts, but is in line with maqasid sharia.